KEANEKARAGAMAN TANAMAN BERPOTENSI SEBAGAI AFRODISIAK ALAMI - Zulkarnain Zulkarnain; St Aisyah Sijid; Syarif Hidayat Amrullah; Rusmadi Rukmana (Teknosains, 2022)
Aphrodisiac is a compound that has the potential to increase sexual desire. Some of these compounds come from the group of flavonoids, alkaloids, and also steroidal saponins which are found in several types of plants. Among the plants that have potential as natural aphrodisiacs are tough bamboo shoots (Gigantochloa nigrociliata), katuk leaves (Sauropus androgynus (L) Merr.), purple eggplant (Solanum melongena L), Javanese chili (Piper retrofractum Vahl), young areca nut. (Areca catechu L), bitter melon (Momordica charantina L.), basil (Ocimum bacilicum), pepper (Piper nigrum), passion fruit seed (Passiflora ligularis Juss). The potential of these plants as natural aphrodisiacs was obtained from testing on experimental animals in the form of mice (Mus musculus) with several treatments and analysis.